Optimize TSP using Ant Colony System using Java - Shatha Habeeb; Zainab Sadiq (Journal of Madenat Alelem University College, 2013)
The travelling salesman problem (TSP) probably is the most prominent problem in combinatorial optimization. It is simple definition along with its notorious difficulty has stimulated many efforts to find an efficient algorithm. In this research use Ant Colony System to solving TSP and generating good solutions to both. The work has been extended to calculate the correlation coefficient between the number of nodes and number of iterations.